Medical and Care Compunetics 6 - Bos, Lodewijk (IOS Press, 2013)
Medical and care compunetics is the field which deals with the social, societal and ethical implications of computing and networking in relation to health care. This book presents proceedings from the seventh annual conference of the International Council on Medical and Care Compunetics (ICMCC); the focus for knowledge exchange in this subject. ICMCC follows, by its nature, a multidisciplinary approach, and the subjects covered in the book are of interest not only to health professionals, but also to a wide range of those involved in health issues such as politicians, supporting specialists, administrators, researchers and developers – not forgetting the patients themselves. Some of the topics presented include: system design and evaluation, computer assisted learning, knowledge representation and ontologies, electronic health records and patient empowerment. The book represents a comprehensive overview of in depth, first hand information, and introduces new developments and advanced systems, technologies and applications to an international audience.